REVITALISASI PERAN MUHAMMADIYAH DALAM BIDANG POLITIK, EKONOMI, DAN PEMBERDAYAAN PEREMPUAN - Wulandari Arif, Qhanita; Helvi Mei Hamka, Waode; Haliq As`sam, Muhammad; Lama Bawa, Dahlan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Muhammadiyah is a modern Islamic organization that plays a strategic role in the life of the nation and state in Indonesia. Since its founding, Muhammadiyah has been committed to integrating Islamic values ​​with evolving social realities. The development of globalization, digitalization, and increasingly complex social, political, and economic dynamics demand the strengthening and renewal of Muhammadiyah's role to remain relevant, adaptive, and able to respond to the challenges of the times. In this context, Muhammadiyah functions not only as a religious organization, but also as a civil society force that contributes to national development. This study aims to analyze the rise of Muhammadiyah's role in national politics, the national economy, and women's empowerment. This study uses a descriptive qualitative approach with a literature review method from various scientific sources, journal articles, and official Muhammadiyah documents published in the last five years. The results show that Muhammadiyah plays a moral role in national politics by maintaining public morality, democratic values, and the basic principles of social justice. In the economic field, Muhammadiyah contributes by developing charitable enterprises based on Sharia law and promoting independence, economic equality, and community welfare. At the same time, Muhammadiyah, through its independent organization, Aisyiyah, plays an active role in women's empowerment through education, health, economics, and women's rights advocacy. The revival of Muhammadiyah's role in these three areas is crucial to strengthening the organization's contribution to building a progressive, just, and civilized Islamic society in the contemporary world.